1967
DOI: 10.1139/b67-218
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Near-Ultraviolet Light and Temperature on Sporulation of the Fungi Alternaria, Cercosporella, Fusarium, Helminthosporium, and Stemphylium

Abstract: Alternaria dauci, A. tomato, Cercosporella herpotrichoides, Fusarium nivale, Helminthosporium catenarium, and Stemphylium botryosum, all Fungi Imperfecti, were grown on temperature gradient plates (5–40 °C) under different regimes of near-ultraviolet radiation (320–420 nm) and darkness. None of the fungi normally sporulated in darkness on the media used. The effects of interaction of temperature and near-ultraviolet radiation (NUV) on sporulation were significant for all six fungi. The fungi were grouped into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
6

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 7 publications
3
24
1
6
Order By: Relevance
“…In the present work, greater sporulation was obtained under alternated regime of light (12 h photoperiod). This alternation simulates conditions required for conidial formation, as conidiophore formation occurs under irradiation and conidium formation during the dark period (Lukens, 1960;Leach, 1967;Waggoner & Horsfall, 1969;Douglas, 1972;Walker, 1980). Wavelengths near 310 ηm, provided by black light, stimulate sporulation of A. solani and the conidiophores do not revert to vegetative hyphae when exposed to the dark, allowing conidial formation (Aragaki et al, 1973).…”
Section: The Adapted and Validated Protocol Allowed Efficient Inductimentioning
confidence: 99%
“…In the present work, greater sporulation was obtained under alternated regime of light (12 h photoperiod). This alternation simulates conditions required for conidial formation, as conidiophore formation occurs under irradiation and conidium formation during the dark period (Lukens, 1960;Leach, 1967;Waggoner & Horsfall, 1969;Douglas, 1972;Walker, 1980). Wavelengths near 310 ηm, provided by black light, stimulate sporulation of A. solani and the conidiophores do not revert to vegetative hyphae when exposed to the dark, allowing conidial formation (Aragaki et al, 1973).…”
Section: The Adapted and Validated Protocol Allowed Efficient Inductimentioning
confidence: 99%
“…Ribeiro et al (1976) found that under a 12 h Iight/12 h dark regime, irradiation in the band 312-440 nm stimulated sporangium production by Phytophthora capsici Leonian and P. palmivora (Butler) Butler, but they did not test the effect of continuous irradiation. Leach (1967) pointed out that for some fungi, near-u. v. light can stimulate the inductive phase but inhibit the terminal phase of sporulation.…”
Section: Discussionmentioning
confidence: 99%
“…It was recognized for fungi such as Alternaria, Cercospora, Fusarium, Helminthosporiurn and Sternphylium (Aragaki 1962;Leach 1967;Honda and Sakamoto 1968;Onesirosan and Banttari 1969;Vakalounakis and Christias 1981), B. squamosa (Bergquist et al 1972) and Verticillium agaricinum (Osman and Valdon 1979). The sporulation of colonies of B. cinerea is affected by light as well.…”
Section: Effects Of Light On Conidiationmentioning
confidence: 99%